Modeling and simulation analysis of Starlink constellation communication - LI Yuanlong, LI Zhiqiang (Zhihui kongzhi yu fangzhen, 2023)
Starlink is the only giant constellation in low Earth orbit currently being rapidly deployed. This paper analyzes the advantages and characteristics of low orbit satellite communication and summarizes Starlink construction and system architecture. The Satellite Toolkit (STK) is used to model and simulate 1 584 satellites of the first stage "Group 1". Then, according to the networking mode of Starlink satellite equipped with laser communication payload, Dijkstra algorithm is used to solve the shortest inter-satellite communication link distance between any two Starlink satellites. Thus, the theoretical shortest communication delay is calculated. The average communication delay from Hawaii Camp Smith to the Yokota Air Base is 42.700 749 2 ms. Based on the simulation results, the military application of Starlink in communication is predicted.